Changes in heart rate during headstand in water - Onodera, S.; Yoshioka, A.; Hayashi, S.; Saito, T.; Wada, T.; Murata, M.; Tsuchida, Y.; Watanabe, V.; Goto, M.; Takagi, Y.; Nose, Y.; Takahara, T.; et al. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A previous study showed that heart rate (HR) significantly decreased during standing while in water, and that the phenomenon depended on the depth of immersion. A headstand posture is often assumed during synchronised swimming. However, it is uncertain whether changes in HR during a headstand position in water are the same as those while in a standing position. In this study, we determined the changes in HR during a headstand posture in water. Ten healthy Japanese males volunteered for this study and provided their informed consent prior to their participation. Measurements were conducted under two conditions, on land and in water, in a random order. Each subject maintained a headstand position on land or in a swimming pool for one min. While in water, the subjects breathed through a compressed gas cylinder used for scuba diving. Water depth was set at a subject's waist level. Water and room temperatures were maintained at 30°C and 28°C, respectively. HR was continuously measured using a waterproof HR monitor. HR rapidly decreased within 18 seconds from the beginning of a headstand posture while in water and was subsequently maintained at a steady state. The changes in HR while in the water were statistically significant interaction (by Repeated two-way ANOVA, p < 0.05). By comparison, HR responses while on land decreased until18 seconds and then showed a minimal increase. HR when in water (55± 5 bpm) was significantly lower than when on land (68 ± 7 bp m; p < 0.05). Our results showed that HR decreased during a headstand while in water, which could be attributed to the diving reflex and an increase in venous return.